Correlation dependence between exactness of firing and morfofunctional indicators of young biathlonists aged 15-16 - V'yacheslav Mulik (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to define grade correlation of exactness of firing and morfofunctional data of young biatlonists aged 15-16. Material and Methods: correlation connection of exactness of firing in lying and up right position in biathlon with indexes of lengths and weight of body, lengths of hand, shoulder, hip and crus, excursion of thorax; deadlift barbell and dynamometry of right and left hands, amount of waves and amplitude of tremor is represented in the article. Results: correlation between exactness of firing regarding to the indices of long of forearm (r=0,73), hip (r=-0,88), crus (r=-0,93), between indexes of deadlift barbell (r=0,53) regarding to the amplitude of tremor (r=-0, 75) is determined. Conclusions: the following factors have influence on the results of biatlonists firing: objective - illumination of targets, strength, speed and wind's direction, presence of precipitation during firing; subjective speed of approaching to the firing-line, indices of heart rate before firing, pace, rhythm and sequence of firing, right position for firing and selection of sighting devices depending on the weather, functional state of neuromuscular system and visual analyzer, sportsman's anthropometric data.